2013
DOI: 10.1021/am404365r
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Mechanisms of Ethylene Carbonate on Si Anodes of Lithium-Ion Batteries: Effects of Degree of Lithiation and Nature of Exposed Surface

Abstract: Ab initio molecular dynamics simulations are used to identify mechanisms of reduction of ethylene carbonate on Si surfaces at various degrees of lithiation, where the low-coordinated surface Si atoms are saturated with O, OH, or H functional groups. The lowest Si content surfaces are represented by quasi-amorphous LiSi4 and LiSi2; intermediate lithiation is given by LiSi crystalline facets, and the highest Li content is studied through Li13Si4 surfaces. It is found that ethylene carbonate (EC) reduction mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
107
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 44 publications
16
107
1
Order By: Relevance
“…In the case of Li 13 Si 4 , such a species receives two extra electrons from the anode surface producing an adsorbed CO 2− anion and a radical anion -OC 2 H 2 O 2− . 64 The EC and VC reduction can also be changed by the nearby salt and a new CO 2 formation pathway for VC was reported. 56 FEC, on the other hand, shows less dependence on the lithium content in Si.…”
Section: In Vivo Modification and Design Of The Seimentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of Li 13 Si 4 , such a species receives two extra electrons from the anode surface producing an adsorbed CO 2− anion and a radical anion -OC 2 H 2 O 2− . 64 The EC and VC reduction can also be changed by the nearby salt and a new CO 2 formation pathway for VC was reported. 56 FEC, on the other hand, shows less dependence on the lithium content in Si.…”
Section: In Vivo Modification and Design Of The Seimentioning
confidence: 99%
“…Leung and Budzien compared EC decomposition on the basal plane of lithiated graphite (LiC 6 ), terminated with =O, -OH and -H and found that C = O edges provide a larger driving force for EC reduction 62 The observation that EC is more inclined to decompose in the presence of oxygen/ hydroxyl termination is consistent with other simulation results. 96 Besides graphite, EC decomposition was simulated on Li, 57,60,97 Si, 45,64,98 and Sn 99 electrodes as well. Due to the lower potential of Li metal than graphite, the decomposition of EC on Li metal is spontaneous and much faster than that on LiC 6 surfaces.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
See 3 more Smart Citations